Model Predictive Control of Cable-Driven Parallel Robot with Cable Sagging: an Assumed Mode Approach - Moussa, Karim; Vie, Antoine; Thieffry, Maxime; Claveau, Fabien; Chevrel, Philippe (International Conference on System Theory, Control and Computing, 2024)
Cable-Driven Parallel Robots (CDPRs) are a type of parallel robots that uses cables to position a moving platform inside its workspace. The cables offer many advantages from an operational point of view, from increasing the size of the workspace to handling heavy loads. However, they raise an issue in modeling their complex physical behavior. Simplifying hypotheses are usually made to facilitate the incorporation of a model in the control law in certain operational conditions, such as straight and massless cables. In this work, a Quasi-Linear Model Predictive Control (QLMPC) is presented based on a flexible cable model and is tested on some challenging scenarios. The cable model is based on the assumed mode approach. A comparison in simulation is made with a model predictive control based on a straight and inelastic cable for an eight-cables 3D suspended CDPR.